2019
DOI: 10.1093/mnras/stz674
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the properties of GMCs in M33 from simulations and observations

Abstract: We compare the properties of clouds in simulated M33 galaxies to those observed in the real M33. We apply a friends of friends algorithm and CPROPS to identify clouds, as well as a pixel by pixel analysis. We obtain very good agreement between the number of clouds, and maximum mass of clouds. Both are lower than occurs for a Milky Way-type galaxy and thus are a function of the surface density, size and galactic potential of M33. We reproduce the observed dependence of molecular cloud properties on radius in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 57 publications
4
22
0
Order By: Relevance
“…Following our analysis of the PHANGS-ALMA pilot sample of 11 galaxies (Sun et al 2018, hereafter S18), we derive these measurements on fixed 90 pc and 150 pc scales using the full PHANGS-ALMA survey, which increases our sample size to 70 galaxies. The derived measurements constitute a benchmark data set that can be readily compared with observations of other types of galaxies or numerical simulations reaching similar spatial resolutions (e.g., Semenov et al 2018;Dobbs et al 2019;Fujimoto et al 2019;Jeffreson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Following our analysis of the PHANGS-ALMA pilot sample of 11 galaxies (Sun et al 2018, hereafter S18), we derive these measurements on fixed 90 pc and 150 pc scales using the full PHANGS-ALMA survey, which increases our sample size to 70 galaxies. The derived measurements constitute a benchmark data set that can be readily compared with observations of other types of galaxies or numerical simulations reaching similar spatial resolutions (e.g., Semenov et al 2018;Dobbs et al 2019;Fujimoto et al 2019;Jeffreson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even if multiple spatial distributions yield the same power spectrum index, our results still a key benchmark for simulations that aim to reproduce Local Group-like galaxies. Several recent works aim to simulate galaxies with properties closely matching the LMC, SMC, M31, M33, or the Milky Way (Combes et al 2012;Wetzel et al 2016;Grisdale et al 2017;Dobbs et al 2018;Garrison-Kimmel et al 2019) with many producing "synthetic" observations to compare with properties found in the actual observations (e.g., Dobbs et al 2019), a key step for directly comparing simulations and observations (Haworth et al 2018). For any simulation the produces dust maps or synthetic IR observations, matching our measured power spectrum represents an important check.…”
Section: Variation In the Power Spectrum Index Between Galaxiesmentioning
confidence: 93%
“…These methods require the value of the density cut, surface density cut, or linking length as an input parameter. They have been used in previous studies of galaxy simulations, and it has generally been found that for an appropriate choice of these parameters, one recovers cloud properties that are in good agreement with observations in the local Universe (Dobbs et al 2011;Hopkins et al 2012;Dobbs & Pringle 2013;Ibáñez-Mejía et al 2017;Hopkins et al 2018;Dobbs et al 2019;Fujimoto et al 2019). However, a cloud definition that is valid for the relatively narrow range of ISM conditions found in nearby galaxies where most GMCs are catalogued (Bolatto et al 2008) may not generalize well to high-redshift conditions.…”
Section: The Case For Studying Bound Cloudsmentioning
confidence: 99%